2021
DOI: 10.1073/pnas.2026676118
|View full text |Cite
|
Sign up to set email alerts
|

Critical Period After Stroke Study (CPASS): A phase II clinical trial testing an optimal time for motor recovery after stroke in humans

Abstract: Restoration of human brain function after injury is a signal challenge for translational neuroscience. Rodent stroke recovery studies identify an optimal or sensitive period for intensive motor training after stroke: near-full recovery is attained if task-specific motor training occurs during this sensitive window. We extended these findings to adult humans with stroke in a randomized controlled trial applying the essential elements of rodent motor training paradigms to humans. Stroke patients were adaptively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 110 publications
4
104
1
4
Order By: Relevance
“…Moreover, these biopsychological factors also influence long term behavior change ( 122 ) and return to work post-stroke ( 123 ). Lastly, there is growing evidence of time and dose-dependent effects of rehabilitation on functional improvement post-stroke ( 124 126 ). As discussed earlier, self-efficacy and motivation influence an individual's engagement in and adherence to rehabilitation, and these factors may therefore also impact the treatment dosage that an individual receives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these biopsychological factors also influence long term behavior change ( 122 ) and return to work post-stroke ( 123 ). Lastly, there is growing evidence of time and dose-dependent effects of rehabilitation on functional improvement post-stroke ( 124 126 ). As discussed earlier, self-efficacy and motivation influence an individual's engagement in and adherence to rehabilitation, and these factors may therefore also impact the treatment dosage that an individual receives.…”
Section: Discussionmentioning
confidence: 99%
“…After 3 months the rate of recovery decreases, but partial recovery is still possible. 45 Subgroup analysis of stroke types showed that recovery of swallowing in ischemic appeared to be superior to hemorrhage. However, the differences were not significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example of the timing of specific and intensive stroke rehabilitation directly translated from rodent experiments to human, showing rehabilitation early within 30 days and late beyond 6 months are not effective. The most effective period has been proven to be 60–90 days ( Dromerick et al, 2021 ). Our experimental work on HUCB and its MNCs treating HIE can be fast-tracked to clinical trials when its availability, dosage and timing are worked out.…”
Section: Discussionmentioning
confidence: 99%